Development of value-added dried pomegranate arils and juice powder: Effects of cultivar, harvest maturity and storage duration of whole fruit - Adetoro, Adegoke Olusesan (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.